Two Cultures and Narration: Biomedical Issues, Art and the Human Being (KULT_online, 2009)
Engineering Life. Narrationen vom Menschen in Biomedizin, Kultur und Literatur (Engineering Life. Narrating the human being in the biomedical, cultural and literary fields) was edited in 2008 by Claudia Breger, Irmela Marei Krüger-Fürhoff and Tanja Nusser. The volume was inspired by an interdisciplinary workshop that took place at the University of Greifswald in 2006, and deals with both narrative strategies in scientific writing and with the presentation of sensitive biomedical issues in literature and film. At the crux of this discussion is modern technology's impact on humankind and the increasing possibilities of manipulating and creating human life. Being researchers from both cultural studies and the empirical sciences, the essays' authors address the subject from a duly interdisciplinary perspective.